Alterations in the Gill Filaments and Secondary Lamellae of Cirrhinus mrigala Exposed to "Nuvan, " an Organophosphorus Insecticide. (23rd October 2014) - Srivastava, Nidhi; Kumari, Usha; Rai, Amita Kumari; Mittal, Swati; Mittal, Ajay Kumar
Abstract : The alterations in the epithelium of the gill filaments and the secondary lamellae of the gills of Cirrhinus mrigala, on exposure to "Nuvan, " have been explored in the present investigation using light and scanning electron microscopy. The fishes were exposed to two sublethal concentrations, 5 mg/L and 15 mg/L, of "Nuvan." The changes are more rapid and intensive at higher concentration than at lower concentration, suggesting that the changes are dose dependent. Increase in thickness of epithelium covering secondary lamellae, merger of epithelium of gill filaments and adjacent secondary lamellae, and aneurysm is considered to reduce efficiency of gills for gaseous exchange. A significant decline in the density and area of the mucous goblet cells in the epithelium of the gill filaments and the secondary lamellae of C. mrigala exposed to "Nuvan" could be correlated with excessive loss of the secretory contents of these cells, uncompensated by their production in sufficient quantities. The histopathological changes, in general, take longer time to recover in the fishes exposed to 15 mg/L than those exposed to 5 mg/L indicating that the changes in fishes exposed to higher concentration are more severe than those at lower concentration of the insecticide.